PENYULUHAN PEMBUATAN KUE BOLU KATUK (Sauropus androgynous) - Nurainun, Nurainun; Rahmadani, Diah Suci (Universitas Muhammadiyah Tapanuli Selatan, 2020)
Semetung Hamlet, Kec. Taman Rajo, Muara Jambi has a lot of potential natural resources, one of which grows katuk. However, the community, especially PKK mothers, does not yet have the knowledge and skills to use katuk leaves as an addition to making sponge cakes. Community service aims to: (1) provide counseling about katuk leaf plants and their properties; (2) practice the skills to make katuk leaf sponge cake; (3) practice skills in packaging sponge cakes. The method used is training and a hands-on approach. The program implementing team was from the pharmacy study program students of STIKes Harapan Ibu Jambi. The results of community service are increasing knowledge about katuk leaf plants; participants are skilled in making katuk leaf sponge cakes; participants are competent in packaging katuk leaf sponge cakes. The program implemented has a positive impact on the citizens, which can see from the increase in knowledge and skills of PKK mothers in Semetung village.